Alignment of undergraduate pharmacology learning outcomes with healthcare practitioner workplace competencies - Du Toit, Pieter Hertzog (University of Pretoria, 2025)
Thesis (PhD (Curriculum and Instructional Design and Development))--University of Pretoria, 2025.